Perception of Locus of Control, Level of Education, Machiavellianism and Ethical Reasoning Against Auditor Behavior in Audit Conflict Situations - Widya Ais Sahla; Emy Iryanie (AKRUAL: JURNAL AKUNTANSI, 2018)
This study aims to examine individual factors such as locus of control (LOC), level of education, Machiavellianism and ethical reasoning that may influence the behavior of auditors in conflict situations. The survey was conducted by using questionnaires to auditors working at Public Accounting Firm in South Kalimantan. The analysis technique used is with multiple regressions. The results show that individual factors such as locus of control (LOC), level of education, Machiavellianism and ethical reasoning have been shown to significantly affect auditor behavior in conflict situations.